Propuesta para disminuir el desperdicio de fibra de Algodón al momento de utilizar el pabilo en el área de hilas, Terminado el proceso de Estirado en la Empresa Textil S.J. Jersey - Pérez Flores, Diego Javier (2015)
In the present work is to study the process of lint developed by the company SJ Ecuadorian CA Jersey, to determine the efficiency in the production of wire, it is structured that: Chapter 1, Generalities. Within the scope of this chapter to be achieved with the research undertaken, objectives, rationale, assumptions and methodology were established. Chapter 2, Theoretical framework. In which basic aspects of the textile industry is detailed in Ecuador, so basics such as spinning and spinning, and processes are established for the development of these activities is belonging Ecuadorian textile industry. Chapter 3, the Company. Within this chapter situational historical theory factory develops SJ Jersey Ecuadorian CA, so we proceed to explain features as its background, objectives and organization, to further develop the current status of it, concluding with the identification of problems.